Molecular Characterization Of Vibrio Species Isolated From Seawater - Yuherman (2001)
A study was conducted to determine the prevalence of Vibrio species in seawater samples obtained from the coast of Malacca, Penang (Batu Feringgi , George Town), and Terengganu, respectively. Four Vibrio cholerae 0139, 10 V. cholerae non-O1, 7 V. cholerae O1 , 160 Vibrio parahaemolyticus, and 57 Vibrio vulnificus strains were isolated from 240 seawater samples 4/32 (0.13%), 3/32 (0 09%), 2/32 (0.06%), and 24/32 (0.75%) seawater samples obtained from Malacca were positive for V. cholerae O 139, V. cholerae non-O1, V. cholerae O1 , and V. parahaemolyticus strains, respectively. 6/30 and 7/30 seawater samples obtained from Batu Feringgi and George Town beaches were positive for V. parahaemolyticus, strains, respectively. All the V. parahaemolyticus strains were Kanagawa-negative. Fifty seven V. vulnificus strains of biotype 1 were isolated from II ( 18.33%) of 60 seawater samples obtained around Marang beach (Terengganu). The antibiotic resistance patterns of all Vibrio species strains tested showed that all were resistant to one or more of the antibiotics tested.